Deputados estaduais e democracia: Valores políticos das elites parlamentares paulista e paranaense - De Almeida Felisbino, Riberti; Kerbauy, Maria Teresa Miceli [UNESP] (FapUNIFESP (SciELO), 2013)
After 20 years of reestablished democracy in Brazil, what do the state legislators think about the regime? The goal of the article is to show the views of state legislators of the Legislative Assemblies of the States of São Paulo and Paraná on democracy. For the views we use a structured and self-administered questionnaire. The results show that for the state legislators: i) democracy is stable, ii) it is superior to any other kind of regime, iii) it's support comes from some public policy and the use of voting and iv) parties and elections are important for democracy.
Keywords: Democracy; Parliamentary elite; Political attitudes; State legislator